Dry Eye Disease: Oxidative Stress on Ocular Surface and Cutting‐Edge Antioxidants - Rong Hu; Jian Shi; Can‐Ming Xie; Xiao‐Lei Yao (Global Challenges)
Abstract Dry eye disease (DED), a multifactorial ocular surface disorder characterized by tear film instability, is pathologically linked to oxidative damage. The accumulation of reactive oxygen species (ROS) across ocular tissues not only directly damages nucleic acids, proteins, and lipids, but also functions as an upstream driver of inflammation and tear hyperosmolarity, collectively disrupting cellular homeostasis. This review comprehensively delineates the mechanistic interplay between oxidative stress (OS) and DED pathogenesis, synthesizing evidence on enzymatic/ nonenzymatic antioxidant alterations in samples of corneal, lacrimal, conjunctival, meibomian gland, and tear tissues, alongside quantitative profiling of OS biomarkers, such as 4‐hydroxynonenal (4HNE), malondialdehyde (MDA), 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG), and 3‐nitrotyrosine (3‐NT). Furthermore, the therapeutic mechanisms of clinically approved and investigational antioxidants, including SKQ1, rebamipide, mitoquinone, elamipretide, lactoferrin, nanozymes, graphene quantum dots, tetrahedral frame of nucleic acids, and Chinese medicine monomers are critically evaluated. With the changes in the modern social environment and lifestyle, the influence of OS on DED is gradually expanding. Antioxidant‐based interventions are poised to become cornerstone components of multimodal DED management strategies.